JBSP : a BSP programming library in Java - Gu, Yan. (2008)
General purpose parallel computing systems come in a variety of forms, among which there are distributed memory multiprocessors and shared memory architectures. Over the past few years, the focus of the parallel computing community is gradually moving from those expensive parallel computers to networked computers. This move has been accelerated with the increase in network computers' computing power as well as the wide spread of Java programming language which supports the concept of "Write once run anywhere". To make parallel computing similar to the normal form of computing, Valiant proposed the BSP (Bulk Synchronous Parallel) model which describes parallel computers in general. Some BSP libraries have been implemented in Fortran, C, and C++. This thesis will report on the development of a Java-based Bulk Synchronous Parallel (JBSP) system.